Risk indicators for early childhood caries in Taiwan - Tsai AI, Chen C-Y, Li L-A, Hsiang C-L, Hsu K-H. (Blackwell Synergy, 2006)
The purpose of this study was to investigate the prevalence, patterns, and etiological factors for caries in children